Harmonizing Fiqh Education with Local Wisdom: Enhancing Students' Religious Awareness via Teacher-Parent Collaboration - Lubis, Winda Nurul Hazizah; Arlina, Arlina (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
This research aims to determine the collaboration between fiqh teachers and parents in increasing students' awareness of worship at MTs Istiqlal Deli Tua. This research is qualitative research with a descriptive approach. This research was carried out at MTs Istiqlal Deli Tua with research subjects namely fiqh teachers, parents and students. Data collection techniques in this research were carried out using interviews, observation and documentation. Meanwhile, the data analysis used is qualitative which is carried out through several stages, namely data collection, data reduction and drawing conclusions. The results of this research are the collaboration between fiqh teachers and parents in increasing students' awareness of worship at MTs Istiqlal Deli Tua, namely teacher interaction with students, advising children, providing good role models, inviting and practicing, giving gifts as a form of appreciation and giving punishment. From the research results, it appears that fiqh teachers have a big role in guiding students in worship and providing good role models. The implication is the need to strengthen the role of fiqh teachers as models and spiritual guides for students.